Import Competition and Informal Employment: Empirical Evidence from China - Feicheng Wang; Zhe Liang; Hartmut Lehmann (Institute of Labor Economics (IZA), 2021)
This paper investigates the effects of trade liberalisation induced labour demand shocks on informal employment in China. We employ a local labour market approach to construct a regional measure of exposure to import tariffs by exploiting initial differences in industrial composition across prefectural cities and then link it with the employment status of individuals. Using three waves of household survey data between 1995 and 2007, our results show that workers from regions that experienced a larger tariff cut were more likely to be employed informally. Further results based on firm-level data reveal a consistent pattern; tariff reductions increased the share of informal workers within firms. Such effects are more salient among smaller and less productive firms. Our findings suggest an important margin of labour market adjustment in response to trade shocks in developing countries, i.e. employment adjustment along the formal-informal dimension.
Keywords: F14; F16; F66; J46; 330; trade liberalisation; import competition; informal employment; firms; China